Agricultural soil pollution due to climate change - Janah, Solihatun; Masjud, Yunita Ismail (Holistic: Journal of Tropical Agriculture Sciences, 2024)
The agricultural sector is very important for human life because of its role for economic purposes and meeting food needs. The use of land for agricultural activities cannot be avoided because humans need food every day. The agricultural sector has a negative impact on soil conditions due to excessive use of fertilizers and water. Objectives: The purpose of this study is to determine the impact of climate change (climate change) on soil pollution. Method and results: The method used for this paper is a qualitative approach with a descriptive explanation. Conclusion: Climate change has an effect on temperature, rainfall, and sea level. The earth's temperature will increase, and there will be extreme rain and extreme weather, while the impact on sea water will increase sea level. This condition can cause flooding, flooding will erode the soil surface resulting in a decrease in soil quality. Pollution due to waste will cause soil pollution and have an impact on rising temperatures.